2007
DOI: 10.1177/0265659007080677
|View full text |Cite
|
Sign up to set email alerts
|

Interactional style, elicitation strategies and language production in professional language intervention

Abstract: This paper explores language intervention for children with specific language impairment in Sweden. The elicitation strategies, style of interaction and language production used by speech and language pathologists (SLPs) were analyzed in two conditions, free conversation and training of grammar. In training, the grammatical targets were used significantly more often by the SLPs, but not by the children. In the free conversations the children talked more and had significantly higher mean length of utterance in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 15 publications
1
6
1
2
Order By: Relevance
“…All four had a history of DLD diagnosed by an SLT at or before age 4. The children took part in a longitudinal research project (Bruce et al, 2007, 2012). The background descriptions for the present study are from two points in time: at age 4–5 (time I) and at age 9–10 (time II).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All four had a history of DLD diagnosed by an SLT at or before age 4. The children took part in a longitudinal research project (Bruce et al, 2007, 2012). The background descriptions for the present study are from two points in time: at age 4–5 (time I) and at age 9–10 (time II).…”
Section: Methodsmentioning
confidence: 99%
“…Bruce et al (2007) studied how speech and language therapists (SLTs) adapt their interactional style in communication with preschool children with DLD in two different contexts: language training and free conversation. In the free conversation context, the children talked more and had a higher mean length of utterance, whereas the SLTs did not vary their amount of talk, or their number of questions between the two contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Recasts cannot occur without a platform utterance, so the clinician's ability to elicit platform utterances also affects treatment outcome. In a study on elicitation strategies and interactional style, Bruce et al (2007) state that there are many strategies to elicit platform utterances, such as "Yes/No question[s]" and "Repetition/Imitation" (p. 258). Bruce et al (2007) found that clinicians used different types of elicitation strategies with different children and in different contexts, suggesting that clinicians adjust to each child, rather than remaining relatively constant with all children.…”
Section: Clinician Factors Related To the Success Of Conversational Rmentioning
confidence: 99%
“…In a study on elicitation strategies and interactional style, Bruce et al (2007) state that there are many strategies to elicit platform utterances, such as "Yes/No question[s]" and "Repetition/Imitation" (p. 258). Bruce et al (2007) found that clinicians used different types of elicitation strategies with different children and in different contexts, suggesting that clinicians adjust to each child, rather than remaining relatively constant with all children. Bruce et al (2007) also found that clinician factors such as speech rate, the frequency of feedback, and overall responsiveness affected children's language output.…”
Section: Clinician Factors Related To the Success Of Conversational Rmentioning
confidence: 99%
See 1 more Smart Citation